Organizational Commitment in Malaysian Public University: An Evidence via Social Network Analysis - Nur Syahidah, Yusoff; Maman Abdurachman, Djauhari; Shamshuritawati, Sharif; Ebi Shahrin, Suleiman (IJENS, 2012)
This paper deals with social network approach to understand an organizational management problem in Malaysian public university. Four groups of factors, i.e., workplace spirituality, affective commitment, continuance commitment and normative commitment are used to quantify the level of organizational commitment. In total, there are 40 characteristics representing those factors. Based on the approach it is evidence that work are spirituality and effective commitment should be more attention by the university management. Each characteristic is considered as a member of social group and the relationship among them as social relationship.